THE RELATIONSHIP AMONG SELF CONCEPT, HOME LEARNING ENVIRONMENT, AND UTILIZATION OF LEARNING RESOURCES WITH MATHEMATICS LEARNING OUTCOMES IN CLASS VIII - Annastasya Dharmawati; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2018)
Low student learning outcomes are associated with many factors. The Self-concept, learning environment, and utilization of learning resources are three factors that allegedly relate to learning outcomes. This study is purposed to determine whether or not a positive and significant correlation self-concept, home learning environment, and utilization of learning resources with mathematics learning outcomes in class VIII State Junior High School 1 Purwareja (SMP Negeri 1 Purwareja) – Klampok Banjarnegara odd semester academic year 2017/2018. The sample class in SMP Negeri 1 Purwareja – Klampok in the academic year 2017/2018 consists of 8 classes. The class sample is class VIII G, chosen by using a random sampling technique. Data collection techniques used questionnaires and tests. The data collection instrument uses a self-concept questionnaire, questionnaire of home study environment, questionnaire of learning resource utilization, and test of learning result. Test of research instrument used validity test, differential test, and reliability test. The prerequisite analysis tests include normality tests, linearity tests, and independent tests. Data analysis for hypothesis testing used simple correlation analysis and multiple regression analysis. The research results show a positive and significant relationship between self-concept, home study environment, and the utilization of learning resources with the results of learning mathematics. At the significant level 5%, dan , with multiple correlation coefficients, and multiple regression equations are three variables . The value of Relative contributions with its double determinantcoefficient0,297 and its effective contribution .